ART LIBRARIES ASSOCIATIONS AND BIBLIOMETRIC ANALYSIS OF ART DOCUMENTATION JOURNAL - Aka, Neslihan; Zan, Burcu Umut (Sadık Hacı, 2025)
The formation of art has a deep-rooted history dating back to prehistoric times and has manifested in different forms throughout human history. Over time, various branches of art have emerged in parallel with social, cultural, and technological developments; the artworks, which are products of these branches, have also diversified in form and content. With the invention of the printing press, the increase in printed publication production led to a significant rise in the number of art-related books; this situation contributed to the growing interest in art collections. The need for systematic organization, preservation, and provision of access to art-related information sources, as well as their dissemination to researchers and art enthusiasts, has gradually paved the way for the emergence of a separate field of expertise. In this context, art librarianship has developed as a specialized area within the discipline of library science. The ability to provide art-focused information services tailored to the needs of users conducting research in the field of art has become possible through the recognition of the importance of art libraries and art librarianship. In line with this awareness, various professional associations have been established in different countries; within these associations, official bulletins and publication organs in different categories have emerged. The aim of this study is to provide a general framework on art librarianship and art library associations for users conducting research in the field of art, and to analyse the bibliometric data of the Art Documentation journal, which is published by the Art Libraries Society of North America (ARLIS/NA) and is one of the leading periodicals in the field of art librarianship. Bibliometric methods were used to answer the research questions. Within the scope of this analysis, the aim is to examine the relationships between publications in the journal content, reveal the citation potential of the journal, and identify the leading authors and main subject areas that form its intellectual structure. The purpose of this study is to provide a general framework for art librarianship and art library associations for users conducting research in the field of art, and to analyse the bibliometric data of the Art Documentation journal, which is published by the Art Libraries Society of North America (ARLIS/NA) and is one of the leading periodicals in the field of art librarianship. The analysis aims to examine the relationships between publications in the journal content, reveal the citation potential of the journal, and identify the leading authors and main subject areas that form its intellectual structure. The study results indicate that there was no significant fluctuation in the journal's annual publication numbers, but there was an increase in citation counts, especially from 2013 onwards. It was observed that open access articles received more citations. The keywords of the studies published in the journal cover various art disciplines such as art history, museum, exhibition, gallery, architecture, and visual literacy, reflecting the multidimensional nature of the field of art librarianship. It is considered that the findings obtained will be guiding for art library users and researchers in this field.

Sanatın oluşumu, tarih öncesi dönemlere kadar uzanan köklü bir geçmişe sahiptir ve insanlık tarihinin her evresinde farklı biçimlerde tezahür etmiştir. Zaman içinde, toplumsal, kültürel ve teknolojik gelişmelere paralel olarak çeşitli sanat dalları ortaya çıkmış; bu dalların ürünleri olan sanat eserleri de biçimsel ve içeriksel olarak çeşitlenmiştir. Matbaanın icadıyla birlikte, özellikle basılı yayın üretiminde yaşanan artış, sanatla ilgili kitapların sayısında da belirgin bir yükselişe yol açmış; bu durum, sanat koleksiyonlarına yönelik ilginin artmasına katkı sağlamıştır. Sanatla ilgili bilgi kaynaklarının sistematik bir biçimde düzenlenmesi, korunması, erişime sunulması ve araştırmacılar ile sanatseverlere ulaştırılması ihtiyacı ise zamanla ayrı bir uzmanlık alanının doğmasına zemin hazırlamış ve bu bağlamda sanat kütüphaneciliği, kütüphanecilik disiplininin özel bir alanı olarak gelişim göstermiştir. Sanat alanında araştırma yapan kullanıcıların ihtiyaçlarına yönelik sanat odaklı bilgi hizmetlerinin sunulabilmesi, sanat kütüphanelerinin ve sanat kütüphaneciliğinin öneminin anlaşılmasıyla mümkün olmuştur. Bu farkındalık doğrultusunda, farklı ülkelerde çeşitli mesleki dernekler kurulmuş; bu dernekler bünyesinde resmi bültenler ile farklı kategorilerde yayın organları ortaya çıkmıştır. Bu çalışmanın amacı, sanat alanında araştırma yapan kullanıcılar için sanat kütüphaneciliği ve sanat kütüphane derneklerine ilişkin genel bir çerçeve sunmak ve Kuzey Amerika Sanat Kütüphaneleri Derneği (ARLIS/NA) tarafından yayımlanan, sanat kütüphaneciliği alanında öncü süreli yayınlardan biri olan Art Documentation dergisinin bibliyometrik verilerini analiz etmektir. Araştırma sorularının yanıtlanabilmesi amacıyla bibliyometrik yöntem kullanılmıştır. Söz konusu analiz kapsamında, dergi içeriğindeki yayınlar arasındaki ilişkilerin incelenmesi, derginin atıf potansiyelinin ortaya konulması ile birlikte entelektüel yapısını oluşturan önde gelen yazarların ve temel konu alanlarının belirlenmesi hedeflenmektedir. Bu çalışmanın amacı, sanat alanında araştırma yapan kullanıcılar için sanat kütüphaneciliği ve sanat kütüphane derneklerine ilişkin genel bir çerçeve sunmak ve Kuzey Amerika Sanat Kütüphaneleri Derneği (ARLIS/NA) tarafından yayımlanan, sanat kütüphaneciliği alanında öncü süreli yayınlardan biri olan Art Documentation dergisinin bibliyometrik verilerini analiz etmektir. Analiz kapsamında, dergi içeriğindeki yayınlar arasındaki ilişkilerin incelenmesi, derginin atıf potansiyelinin ortaya konulması ile birlikte entelektüel yapısını oluşturan önde gelen yazarların ve temel konu alanlarının belirlenmesi hedeflenmektedir. Çalışma sonucunda, derginin yıllık yayın sayısında belirgin bir dalgalanma olmadığı, ancak atıf sayılarında özellikle 2013 yılından itibaren artış yaşandığı belirlenmiştir. Açık erişim makalelerin daha fazla atıf aldığı gözlemlenmiştir. Dergide yayımlanan çalışmaların anahtar kelimeleri, sanat tarihi, müze, sergi, galeri, mimarlık ve görsel okuryazarlık gibi çeşitli sanat disiplinlerini kapsamakta olup, sanat kütüphaneciliği alanının çok boyutlu yapısını yansıtmaktadır. Elde edilen bulguların, sanat kütüphaneleri kullanıcılarına ve bu alanda araştırma yapacak bilim insanlarına yol gösterici nitelikte olduğu değerlendirilmektedir.
SANAT KÜTÜPHANELERİ DERNEKLERİ VE ART DOCUMENTATION DERGİSİNİN BİBLİYOMETRİK ANALİZİ
Keywords: Sociology of Culture; Kültür Sosyolojisi